Inclusive Madrasah: Concepts, Approaches, and Policies - Anshari, M. (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
One of the stigma and prejudice on people with disabilities arise in the educational setting, madrasah as Islamic educational institutions have contributed to exclusion and marginalization of muslim student with disabilities. Referring to the source from the education Management information System (EMIS) of The Kementerian Agama of the Republic of Indonesia in 2021 its shows the number of Madrasah in Indonesia 83,648 madrasah, there are only several of madrasah that have implemented inclusive madrasah. This paper focuses on inclusive education in the context of Islamic educational institutions in madrasah, which is related to policies, concepts, and practices. Concepts and practices that have been carried out by a number of madrasah that provide inclusive education grow and develop bottom-up from practitioners and parents who have children with disabilities, and have been carried out by a number of madrasah that provide inclusive education grow and develop top down The Kementerian Agama of the Republic of Indonesia appointed several madrasas as piloting projects for inclusive madrasah. This article attempts to review various studies regarding inclusive madrasah in Indonesia as the concepts, approaches and policies.